Analisis Akuntabilitas Dan Pengawasan Terhadap Kinerja Anggaran Dana Desa Berbasis Value For Money: Studi Empiris Pada Desa Se-Kecamatan Sumbermanjing Wétan Kabupaten Malang - YUSWANTO NUGROHO, ARIEF; SUKMAWATI, SARI (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
Sumberagung Village is the village that receives the most village funds because it is the poorest village in Sumbermanjing Wétan District. Therefore, it is necessary to know about the performance of the value-for-money-based village fund budget and the influence of the factors that can influence it. This research aims to determine the performance of the value-for-money-based village fund budget and its influence on the variables of accountability, transparency, supervision, and a basic understanding of accounting. In this research, the author used quantitative methods. The population used was all village officials in Sumbermanjing Wétan sub-district, Malang, and 60 respondents were used. The data collection was based on surveys and questionnaires. The data analysis techniques used are descriptive statistics, data quality testing, multiple linear regression analysis, and hypothesis testing. The results of this research show a calculated t value of 2.532 > t-table of 2.00488 and a significance value (sig.) of 0.05 > 0.031, meaning that accountability has a positive and significant effect on the performance of the village fund budget. The t-count value is 4.148 > t-table is 2.00488 and the significance value (sig.) is 0.05 > 0.018, meaning that transparency has a positive and significant effect on the performance of the Village Fund budget. The t-count value is 3.018 > t-table is 2.00488 and the significance value (sig.) is 0.05 > 0.013, meaning that participation has a positive and significant effect on the performance of the village fund budget. The t-count value is 4.702 > t-table is 2.00488 and the significance value (sig.) is 0.05 > 0.000, meaning that supervision has a positive and significant effect on the performance of the village fund budget. The t-count value is 3.015 > t-table is 2.00488 and the significance value (sig.) is 0.05 > 0.004, meaning that understanding accounting has a positive and significant effect on the performance of the Village Fund budget.